Cook like a rock star : 125 recipes, lessons, and culinary secrets - Burrell, Anne (Clarkson Potter/Publishers, 2011)
Anne Burrell presents 125 recipes, based on accessible ingredients, and includes notes and tricks to cook more efficiently.